Hubungan antara Tingkat Pengetahuan dengan Perilaku Ibu Dalam Pencegahan Demam Berdarah Dengue: Studi Observasional Analitik di Wilayah Kerja Puskesmas Genuk, Kota Semarang - Rita Kartika Sari; Resky Septiyani; Imam Djamaluddin Mashoedi (Jurnal Ners, 2023)
Dengue Hemorrhagic Fever’s still a health problem in Indonesia, this is due to its increasing prevalence from year to year. Various obstacles can be found to reduce dengue cases, including the level of knowledge and behavior to prevent dengue. The objective of this research was to determine the relationship between the level of knowledge and the behavior of mothers in the prevention of DHF at the Genuk Public Health Center, Semarang. The research was conducted from August 2022 to September 2022. The type of research used was analytic observational with a cross-sectional approach, the number of samples used in this research was 126 samples of mothers who were taken by non-probability sampling with consecutive sampling, and the instrument used was a questionnaire with data analysis using Spearman rho. The results showed that from 126 samples, it was found that mothers who had a high level of knowledge 89.7% respondents, mothers with low knowledge levels 10.3% respondents, and mothers who had good preventive behavior towards dengue prevention were 74.6% of respondents, mothers with poor preventive behavior were 25.4%. Spearman rho test analysis obtained a p-value <0.05 (p = 0.001) so there was a relationship between the level of knowledge and the mother's behavior in preventing DHF, and the r value was 0.2-<0.4 (r = 0.283) with a weak relationship. The results of the bivariate analysis that there was a significant relationship between the variable level of knowledge and the behavior of mothers in preventing DHF.